A model for virtual network embedding using Artificial Bee Colony. (6th April 2018) - Pathak, Isha; Tripathi, Atul; Vidyarthi, Deo Prakash
Summary: In a network virtualization environment, a significant research problem is that of virtual network embedding. As the network virtualization system is distributed in nature, an effective solution on how to optimally embed a dynamically generated virtual network request on the substrate networks that are owned and managed by multiple infrastructure providers needs proper attention. The problem is computationally hard, and therefore, many approaches, implying heuristics/meta‐heuristics, have been applied for the same. A meta‐heuristic, Artificial Bee Colony algorithm is getting popular due to its robustness toward complex problem solving. A novel approach based on Artificial Bee Colony to address the dynamic virtual network embedding problem in a multiple infrastructure provider scenario is proposed in this work. Bee population is initialized by using a greedy heuristic in which the number of substrate networks together with virtual network requests constructs a bee. Generated solution, in the population, is improvised by using greedy selection that explores a local search method adopted by the bees. In greedy selection, the new candidate source is memorized by the bee if its fitness is better than the fitness of the existing source. The performance study of the proposed model is done by simulation over various metrics such as embedding cost, embedding time, and acceptance ratio. A comparative study is conducted with other nature‐inspired virtual network embedding algorithms on these metrics. The findings affirm that the proposed virtual network embedding approach performs well and produces better results. Abstract : The paper presents a novel approach that solves the NP‐hard Virtual Network Embedding problem by applying Artificial Bee Colony in a scenario where multiple substrate networks are managed by multiple infrastructure providers. The proposed Artificial Bee Colony‐based approach provides virtual network embedding solutions in an unknown dynamic network virtualization environment. Comparison of the proposed approach with state of art has been conducted through extensive simulation.